EVIDENCE FROM NORTHWEST EUROPEAN BOGS SHOWS 'LITTLE ICE AGE' CLIMATIC CHANGES DRIVEN BY VARIATIONS IN SOLAR ACTIVITY - Mauquoy D.; Van Geel B.; Blaauw M.; Van der Plicht J. (My University, 2002)
Fluctuations in Holocene atmospheric radiocarbon concentrations have been shown to be due to variations in solar activity. Analyses of both 10Be and 14C nuclides confirm that production-rate changes during the Holocene were largely modulated by solar activity. Analyses of peat samples from two intact European ombrotrophic bogs show that climatic deteriorations during the ‘Little Ice Age’ are associated with transitions to increasing atmospheric 14C content due to greater 14C production. Both ombrotrophic mires, which are positioned c. 800 km apart, register reactions to globally recorded 14C fluctuations between ad 1449 and 1464 and an almost identical reaction between ad 1601 and 1604.